2016
DOI: 10.1016/j.surfcoat.2016.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sprayed coatings for containment of Cu-Mg-Si metallic phase change material

Abstract: The performance of Y 2 O 3 -stabilized ZrO 2 (YSZ), Y 2 O 3 , and Al 2 O 3 plasma sprayed coatings are investigated for their ability to prevent attack of Haynes 230 by a near-eutectic Cu-Mg-Si metallic phase change material (PCM) in a closed environment at 820 °C. Areas where coatings failed were identified with optical and scanning electron microscopy, while chemical interactions were clarified through elemental mapping using electron microprobe analysis. Despite its susceptibility to reduction by Mg, the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…A 100% H 2 atmosphere was omitted, as it was desired to investigate the intermediate stage of HAMR, rather than drive the system to the reducing limit. Note that Y 2 O 3 is more thermodynamically stable than MgO [12]. The present work is thus unable to reduce Y 2 O 3 , however investigating the effect of the oxide species inclusion on the HAMR reduction was still a motivation of the study.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A 100% H 2 atmosphere was omitted, as it was desired to investigate the intermediate stage of HAMR, rather than drive the system to the reducing limit. Note that Y 2 O 3 is more thermodynamically stable than MgO [12]. The present work is thus unable to reduce Y 2 O 3 , however investigating the effect of the oxide species inclusion on the HAMR reduction was still a motivation of the study.…”
Section: Introductionmentioning
confidence: 84%
“…Following reduction, the crucibles were observed to contain a dense white crust, beneath which was a friable black powder. Note that the Alumina (Al 2 O 3 ) crucibles are less thermodynamically stable than MgO [12], indicating that the crucibles may have been reduced during the experiments. However, no Aluminumrelated phases were observed in XRD analysis, and the crucible interiors did not appear to be notably consumed.…”
Section: Initial Stage Hamrmentioning
confidence: 99%
“…Further research by Withey et al (2016) found that a plasma sprayed Al 2 O 3 protective coating (on H230) performed well to prevent this phenomenon. Yan and Fan (2001) also recommended ceramic coatings for steel in the containment of molten aluminium, since nickel dissolves in liquid aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights one of the major challenges when working with Y x Al 1-x N, namely, the high affinity of yttrium to oxidation, especially when compared to aluminum, resulting in yttrium oxide compounds (Y 2 O 3 ). [23] Looking at the Ellingham diagrams for oxidation of both aluminum and yttrium, the Gibbs free energy change for aluminum is in the range from -960 to -1020 kJ mol À1 at 200 °C and from -800 to -850 kJ mol À1 at 1000 °C [24][25][26] compared to -1130 to -1200 kJ mol À1 at 200 °C and from -970 to -1040 kJ mol À1 at 1000 °C for yttrium. [24,25,27] The significantly more negative values of the Gibbs free energy change indicate a higher oxidation affinity of yttrium compared to aluminum, resulting in the aforementioned challenges.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Looking at the Ellingham diagrams for oxidation of both aluminum and yttrium, the Gibbs free energy change for aluminum is in the range from -960 to -1020 kJ mol À1 at 200 °C and from -800 to -850 kJ mol À1 at 1000 °C [24][25][26] compared to -1130 to -1200 kJ mol À1 at 200 °C and from -970 to -1040 kJ mol À1 at 1000 °C for yttrium. [24,25,27] The significantly more negative values of the Gibbs free energy change indicate a higher oxidation affinity of yttrium compared to aluminum, resulting in the aforementioned challenges.…”
Section: Introductionmentioning
confidence: 99%